The occultation of Mars by the Moon on September 6, 2020: contributions of open science to astronomy research - Novais, Maria; Tolentino, Ricardo José Vaz (Cadernos de Astronomia, 2024)
Astronomy arouses interest and captivates the human imagination due to its connection with the deepest existential inquiries that inhabit the mind. The beauty and grandeur of celestial events sparkle the eyes, and for this reason, there are many people who dedicate their time and resources to explore and capture astronomical events. In this article, we describe the occultation of Mars by the Moon, which was captured on September 6, 2020, by the Vaz Tolentino Lunar Observatory. We will also discuss how this passion for science can contribute to the work of researchers in the field and how open access can aid in this process.
Keywords: astronomy; lunar occultation; astrophotography; citizen science; open science